2014
DOI: 10.1002/lary.25110
|View full text |Cite
|
Sign up to set email alerts
|

What drives quality of life in patients with sporadic vestibular schwannoma?

Abstract: Ongoing dizziness and headache are the strongest predictors of long-term quality-of-life reduction in patients with sporadic VS, while the impact of hearing loss, facial nerve function, and tinnitus are less by comparison. This information may be valuable for patient counseling, refinement of VS quality-of-life assessment instruments, and determining high-yield targets for therapy in efforts to further improve patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 27 publications
(28 reference statements)
5
78
3
Order By: Relevance
“…e would like to congratulate Marston et al for their very nice contribution concerning the influence of the growth pattern of sporadic vestibular schwannoma (VS) before stereotactic radiosurgery (SRS) on the growth pattern after SRS. 5 The Mayo Clinic group under the leadership of Bruce Pollock have published 2 of the 5 comparative studies demonstrating the superiority of Gamma Knife radiosurgery (GKS) over microsurgical resection in small-to medium-sized VSs. 8,10 In particular, these 5 studies have demonstrated a much lower risk of motor facial palsy and functional hearing loss with radiosurgery.…”
mentioning
confidence: 99%
“…e would like to congratulate Marston et al for their very nice contribution concerning the influence of the growth pattern of sporadic vestibular schwannoma (VS) before stereotactic radiosurgery (SRS) on the growth pattern after SRS. 5 The Mayo Clinic group under the leadership of Bruce Pollock have published 2 of the 5 comparative studies demonstrating the superiority of Gamma Knife radiosurgery (GKS) over microsurgical resection in small-to medium-sized VSs. 8,10 In particular, these 5 studies have demonstrated a much lower risk of motor facial palsy and functional hearing loss with radiosurgery.…”
mentioning
confidence: 99%
“…This accords with preceding findings in VS patient quality of life, including the results reported by Carlson et al, who identified dizziness, headache, and tinnitus respectively as the primary drivers in the decline in quality of life experienced by VS patients, compared with nontumor controls. 19,20 Age also appears to play a role in how patients experience and respond to VS symptoms. More specifically, older patients frequently present with dizziness as their primary symptom, whereas patients who seek medical attention for headache are significantly more likely to be in the youngest age group.…”
Section: Discussionmentioning
confidence: 99%
“…The existing literature of care that focuses on the patient with AN has mainly highlighted on delineating those symptoms most debilitating for patients, thus guiding treatment decision making and the patient. [22][23][24] However, there are far fewer reports that have analyzed how patients regard their perceived role in the decision-making process of their care and the impact on ultimate outcomes and patient satisfaction. Graham et al analyzed patients newly diagnosed with AN and found that one-fifth of patients experienced significant decisional conflict, based on a validated decisional conflict scale, when presented with initial management options including watchful waiting.…”
Section: Review Of the Literature Of Patient Decision Making In Acousmentioning
confidence: 99%